MODEL OF TEACHING RUSSIAN, WHICH IS ATTACHED TO THE DEVELOPMENT OF SPEECH COMPETENCIES THROUGH THE TECHNOLOGY”LANGUAGE PORTFOLIOS” - Saidjalalova Sayyora Mirsodikovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
This study is devoted to the development and implementation of an innovative model of Russian language teaching aimed at the effective development of students’ speech competences with regard to their future professional activities. The model is based on the application of the technology of «language portfolios», which allows creating an individual learning trajectory for each student. To develop and test the model of Russian language teaching, which will contribute to the formation of students’ all necessary speech skills for successful communication in the professional environment. Modern realities require from university graduates not only deep theoretical knowledge, but also developed communicative skills. The use of «language portfolios» technology allows making the process of Russian language teaching more individual, focused on the practical needs of students and contributing to their successful socialization in the professional environment.